If f : R ➡️R is defined by f(x) = x³ then f-¹ (8) is
equal to
Attachments:
![](https://hi-static.z-dn.net/files/d80/8be83611f59f3070e121ec2e95d5fe3e.jpg)
Answers
Answered by
0
Answer:
i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?
Step-by-step explanation:
i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?i) CH 2 =CH-C=C-CH 3 ponds ?
Similar questions